Child linear growth during and after the first 1000 days is positively associated with intellectual functioning and mental health in school-age children in Vietnam - Nguyen, Phuong Hong; Tran, Lan Mai; Khương, Long Quỳnh; Young, Melissa F.; Duong, Thai Hong (American Society for Nutrition, 2021)
Background: Millions of children fail to meet their developmental potential and experience mental health concerns globally. Evidence is mixed on whether growth beyond the first 1000 d of life influences intellectual functioning and mental health in school-age children. Objectives: We examined associations of childhood growth before and after the first 1000 d of life with child intellectual functioning and mental health at age 6–7 y. Methods: We used data from a follow-up of a randomized controlled trial of preconception supplementation (PRECONCEPT study) in Vietnam. A total of 5011 women participated in the study and 1579 children were born during 2012–2014. At age 6–7 y, child intellectual functioning was assessed using the Wechsler Intelligence Scale for Children, and mental health concerns were measured using the Strengths and Difficulties Questionnaire. Multivariable linear models were used to examine the independent association of child size at age 2 y [height-for-age z-score (HAZ) and body-mass-index z-score (BMIZ)] and conditional measures of linear and ponderal growth between the ages of 2 and 7 y. Results: HAZ at 2 y was positively associated with the Full-Scale Intelligence Quotient (β = 1.4; 95% CI: 0.5, 2.2 points) and its subdomains, namely Perceptual Reasoning Index, Working Memory Index, and Processing Speed Index (β = 1.0–1.4 points). Higher HAZ at 2 y was associated with lower overall mental health concerns (β = −0.24; 95% CI: −0.47, −0.01) and peer problems (β = −0.08; 95% CI: −0.17, −0.01). Faster height gain between 2 and 7 y was associated with higher total intellectual functioning (β = 0.9; 95% CI: 0.02, 1.8) and fewer emotional issues (β = −0.09; 95% CI: −0.18, −0.01). BMIZ at 2 y was not associated with intellectual functioning but was marginally associated with higher conduct and peer problems. Conditional weight gain between 2 and 7 y was not associated with child intellectual functioning or mental health in young school-age children. Conclusions: Child linear growth both during and beyond the first 1000 d is positively associated with intellectual functioning and mental health during the early school-age years.